Effectiveness of the school dental screening programme in stimulating dental attendance for children in need of treatment in Northern Ireland - Donaldson M, Kinirons M (Blackwell Synergy, 2001)
The school dental screening programme has been in existence from the beginning of the 20th century yet its value in encouraging attendance among children with a dental health need is not fully established.